How are students on the autism spectrum affected by bullying? Perspectives of students and parents. Issue 1 (30th May 2018) - Ashburner, Jill; Saggers, Beth; Campbell, Marilyn A.; Dillon‐Wallace, Julie A.; Hwang, Yoon‐Suk; Carrington, Suzanne; Bobir, Natasha
Abstract : Previous research has focused on the prevalence of bullying of students with autism spectrum disorder (ASD), with little attention given to its emotional effect. This mixed methods study examined levels of worry about bullying and bullying experiences reported by students and parents. To determine whether some students with ASD are differentially affected, we explored associations between students' characteristics (understanding of bullying, age and co‐morbid conditions) and their bullying experiences and worries. Surveys exploring bullying experiences and levels of worry about bullying were completed by 89 students with ASD without intellectual disability aged 11–16 years and their parents. We also qualitatively explored parents' perceptions of how bullying affects their children, through semi‐structured interviews of nine parents. Students with comorbid anxiety disorders were more likely to report face‐to‐face victimization and were more troubled by both face‐to‐face bullying and cyberbullying, while students with depression were more likely to report cyber victimization. Parental concerns included the impact of victimization on school attendance, self‐esteem, mental health, social participation, academic performance, and behaviour. The significantly higher levels of worry about bullying and higher victimization rates reported by students with internalizing symptoms suggest that these students may be disproportionately at risk of psychological harm.